PROFIL USAHA DAN PENGELOLAAN PEDAGANG KAKI LIMA DI KAWASAN SIMPANG LIMA DAN TAMAN KB DI KOTA SEMARANG - Reni Shinta Dewi (Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Semarang is one of the business center with the growth of PKL , which grew rapidly. Unfavorableimpression of the city can be generated from the PKL. Therefore this study aimed to assess the characteristics ofthe business profile of PKL in the area of Simpang Lima and Taman KB, characteristics EntrepreunerPsychological capital of PKL in the area of Simpang Lima and Taman KB . This study was conducted to allPKL in the area of Simpang Lima and Taman KB Semarang. This type of research is quantitative descriptiveanalysis. The results showed that most of the traders are food vendors . The location of PKL to Simpang Lima aredivided into three areas: the area in front of the Matahari Mall , Simpang Lima area and Taman KB. Traders inthis area sell for up to eight hours a day.